History of the world map by map - Snow, Peter (Dorling Kindersley Limited, 2018)
More than 140 detailed maps tell the story of pivotal episodes in world history, from the first human migrations out of Africa to the space race. Custom regional and global maps present the history of the world in action, charting how events traced patterns on land and ocean--patterns of exploration, discovery, or conquest that created empires, colonies, or theaters of war. Thoughtful organization of information will help you follow the story of civilizations through ancient, medieval, and modern times. But not every page is full of maps. At key points in History Map by Map, broad, sweeping introductions provide a chance to step back and look at entire periods, such as World War II, or to explore overarching themes, such as the Industrial Revolution. Picture spreads, meanwhile, focus on epoch-defining moments or developments, such as fascism and communism, and the invention of printing